Different Fecal Microbiota in Hirschsprung's Patients With and Without Associated Enterocolitis - Arnaud, Alexis P.; Cousin, Ianis; Schmitt, Françoise; Petit, Thierry; Parmentier, Benoit; Levard, Guillaume; Podevin, Guillaume; Guinot, Audrey; DeNapoli, Stéphan; Hervieux, Erik; Flaum, Valérie; De Vries, Philine; et al. (Frontiers in Microbiology, 2022)
Background and Objectives Patients with Hirschsprung's disease are at risk of developing Hirschsprung-associated enterocolitis, especially in the first 2 years of life. The pathophysiology of this inflammatory disease remains unclear, and intestinal dysbiosis has been proposed in the last decade. The primary objective of this study was to evaluate in a large cohort if Hirschsprung-associated enterocolitis was associated with alterations of fecal bacterial composition compared with HD without enterocolitis in different age groups. Methods We analyzed the fecal microbiota structure of 103 Hirschsprung patients from 3 months to 16 years of age, all of whom had completed definitive surgery for rectosigmoid Hirschsprung. 16S rRNA gene sequencing allowed us to compare the microbiota composition between Hirschsprung's disease patients with (HAEC group) or without enterocolitis (HD group) in different age groups (0–2, 2–6, 6–12, and 12–16 years). Results Richness and diversity increased with age group but did not differ between HD and HAEC patients, irrespective of the age group. Relative abundance of Actinobacteria was lower in HAEC than in HD patients under 2 years of age (−66%, P = 0.045). Multivariate analysis by linear models (MaAsLin) considering sex, medications, birth mode, breast-feeding, and the Bristol stool scale, as well as surgery parameters, highlighted Flavonifractor plautii and Eggerthella lenta, as well as Ruminococcus gnavus group, as positively associated with Hirschsprung-associated enterocolitis in the 0–2 years age group. Conclusion Hirschsprung-associated enterocolitis was associated with features of intestinal dysbiosis in infants (0–2 years) but not in older patients. This could explain the highest rate of enterocolitis in this age group. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT02857205, MICROPRUNG, NCT02857205, 02/08/2016.